Nitrogen balance and mineral nitrogen content in the soil in a long experiment with maize under different systems of N fertilization - J. Balík; J. Černý; P. Tlustoš; M. Zitková (Plant, Soil and Environment, 2003)
The effect of different systems of N fertilization on nitrogen balance and N transformation in the soil was studied in long-term stationary experiments (1991-2002) with successive growing of maize. Average dry matter yield for the control without fertilization in the period 1991-2002 was 11.67 t of dry matter per ha, which was by 2-2.9 t less than for fertilization treatments. Statistically significant differences between the control and fertilization treatments were determined for the first time in the 4th experimental year. Average nitrogen uptake by the aboveground biomass was116 kgN/ha for the control, 162-170 kg N/ha for fertilization treatments. All experimental treatments had a negative balance of N inputs and outputs, and it was -1394 kg N/ha for the control (for 12 experimental years). After the application of mineral fertilizers, a lower content of total carbon and nitrogen was measured in the topsoil compared to the control and treatments with organic fertilization. The changes in the nitrogen regime of soil were characterized by the content of extractable nitrogen and carbon in extractions by 0.01M CaCl2. With respect to the content of mineral nitrogen and easily extractable organic nitrogen and carbon in the topsoil the control was most stable followed by farmyard manure treatment. Soil lysimeters were installed in these experiments (depth60 cm, size0.2 m2). For an eight-year period (1994/2002)11.78 kgN-NO3-/ha were determined in lysimetric waters. These values for fertilization treatments ranged from 21.0 to58.2 kgN-NO3-/ha. Straw application reduced nitrate contents in lysimetric waters.